UJI KONSENTRASI CENDAWAN Beauveria bassiana (Bals.) Vuill TERHADAP MORTALITAS KEPIK POLONG (Riptortus linearis) F. PADA TANAMAN KEDELAI - Rika Aprilia Fajar Riningrum; Nadrawati Nadrawati; Edhie Turmudi (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2020)
[TESTING THE CONCENTRATION OF FUNGI Beauveria bassiana (Bals.) ON MORTALITY OF POD BORER (Riptortus linearis F.) ON SOYBEAN]. To control pod borer (Riptortus linearis F). on soybean using chemical insecticides can cause pollution to the environment, kill non-targeted insects and evolve pest resistance. The use of entomopathogenic fungus is an environmentally friendly alternative, one of which is Beauveria bassiana. (Bals.). The purpose of this study was to obtain an effective concentration of Beauveria bassiana fungi that can kill the pod borer at the 50% level.  The study was arranged in a Completely Randomized Design (CRD) consisting of 6 levels of fungi and 3 replications, where each experimental unit used 2 polybags.  Each treatment unit used 10 pod borers. The concentration of B. bassiana consisted of 105, 106, 107, 108 and 109 conidia / mL, and without fungi application as a control. The results indicated that the treatment of B. bassiana concentration on R. linearis significantly affected the percentage of mortality and the number of infected R. linearis, but no significant effect on the time of death, number of pods/plants and percentage of the number of damaged soybean pods. The mortality of R. linearis is classified as low, that is, less than 50%.